2010
DOI: 10.1158/0008-5472.can-10-0850
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic Acid Reduces Bone Loss and Tumor Growth in an Orthotopic Xenograft Model of Osteolytic Oral Squamous Cell Carcinoma

Abstract: Squamous cell carcinoma (SCC) is the most common form of oral cancer. Destruction and invasion of mandibular and maxillary bone frequently occurs and contributes to morbidity and mortality. We hypothesized that the bisphosphonate drug zoledronic acid (ZOL) would inhibit tumor-induced osteolysis and reduce tumor growth and invasion in a murine xenograft model of bone-invasive oral SCC (OSCC) derived from an osteolytic feline OSCC. Luciferase-expressing OSCC cells (SCCF2Luc) were injected into the perimaxillary … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 45 publications
1
46
0
Order By: Relevance
“…Although little is known as to whether OSCC cells have the ability to resorb bone themselves, it is clear that osteoclasts are much involved in this process [14][15][16]. Osteoclasts differentiate at the bone surface and dissolve mineral components by an extracellular mechanism involving secretion of acid [17,18].…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…Although little is known as to whether OSCC cells have the ability to resorb bone themselves, it is clear that osteoclasts are much involved in this process [14][15][16]. Osteoclasts differentiate at the bone surface and dissolve mineral components by an extracellular mechanism involving secretion of acid [17,18].…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…In conclusion, several preclinical studies have shown that NBPs can reduce tumor growth and invasion in murine allo-and xenograft models of bone-invasive oral squamous cell carcinoma (Cui et al, 2005;Martin et al, 2010). However, no information was provided on whether Ca 2 þ release during bone resorption by oral cancer could enhance the antitumor effects of BPs and contribute to their therapeutic activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely used in bone metastatic cancers to prevent cancer-induced bone diseases (Coleman, 2012). Notably, ZA has been reported to effectively reduce bone loss and tumor growth in a bone-invasive mouse model of OSCC (Cui et al, 2005;Martin et al, 2010). Furthermore, ZA can inhibit the proliferation of OSCC cells in vitro by inducing apoptosis and/or cell cycle arrest (Tamura et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with zoledronic acid was associated with a significant reduction of skeletal-related events and, possibly, direct apoptotic effects in tumour cells. (Martin et al, 2010;Morgan et al, ;Zhang et al, 2010) Our group reported that the anti-tumour agent of marine origin, Trabectedin (Yondelis), was unexpectedly found to be highly cytotoxic to mononuclear phagocytes, including TAMs. This cytotoxic effect is remarkably selective, as neutrophils and lymphocytes were not affected.…”
Section: Tams and Temsmentioning
confidence: 99%